Pendampingan Mewujudkan Global Good Agriculture Practice (GAP) Melalui Penguatan Sertifikasi Halal Bagi Perusahaan Internasional - Masruroh, Nikmatul; Qardhawi, Muhammad Ali Yusuf Al; Anwar, Jufan Afnani; Fadli, Ahmad (Welfare : Jurnal Pengabdian Masyarakat, 2024)
Industrialization today does not only occur in big cities but also in small cities such as Jember Regency. Present in this city is PT. Gading Mas Indonesia Teguh (GMIT), which concentrates on cultivating edamame and carrying out international buying and selling. Based on the experience carried out, the aim of this service is to: first, collaborate in creating an environmentally friendly company; second, carry out a process of strengthening the importance of halal certification for international companies; and third, provide assistance in the Global Good Agriculture Practice (GAP) process for international companies. The method used is the method of direct participation with company employees. Apart from that, it also strengthens halal certification to support the successful fulfillment of GAP for PT. GMIT Jember. Based on the results of this service, PT. GMIT Jember improves product quality by implementing GAP and processing halal certification. Because, based on this assistance, the existence of GAP through halal certification means that PT. GMIT Jember can penetrate the market, following PT. Mitratani Dua Tujuh Jember, both of which are international companies in edamame products.